Oxford illustrated encyclopedia: Vol.9 - Index and ready reference (New York, 1993)
The book contains of additional entries on figures and places relating to the major religions, and to those of oral tradition found around the world. IT also includes entries on people and places which are considered to be mythological, but with form and integral part of our cultural herutage (such as the Greek and Germanic pantheon of gods). The genealogy of supernatural beings of muth and legend is a fluid subject since the ancestry of a well-known figure many mulate according to its narrative source
Keywords: encyclopedias and dictionaries